PENGEMBANGAN BAHAN CERITA ANAK BERBASIS KEARIFAN LOKAL DALAM KEGIATAN LITERASI DI SD NEGERI 1 RENDANG - Sueca, I Nengah; Sri Rusmiati, Ni Komang (Dharmas Education Journal (DE_Journal), 2024)
Literacy skills at the elementary school level have great significance because they are the foundation for the development of their reading, writing and critical thinking abilities. However, in implementing literacy activities, especially in elementary schools, there are still many problems such as a lack of book supplies. Textbooks and story books mostly contain stories from outside the region, which makes it difficult for students to understand them. The main aim of this research is to understand the needs of students and teachers in carrying out literacy activities in the school environment, as well as adding reading material that supports literacy activities for lower grade students at SD Negeri 1 Rendang. This research aims to develop literacy material for lower grade students using stories based on local wisdom, especially stories about Ngelawang in Bali, by applying a research and development approach. This research is limited to four development stages consisting of: 1) Identification of potential problems, 2) Data collection, 3) Preparation of teaching materials, and 4) Validation of literacy materials. The results of validation by experts show that the content score for developing literacy material for low grade students with the story of Ngelawang in Bali is 73, which in the Likert scale formula category is rated as very valid. Apart from that, the average score from the book illustration aspect is 70, also rated as very valid based on the Likert scale formula.